Magnetically-dressed CrSBr exciton-polaritons in ultrastrong coupling regime - Tingting Wang; Dingyang Zhang; Shiqi Yang; Zhongchong Lin; Quan Chen; Jinbo Yang; Qihuang Gong; Zuxin Chen; Yu Ye; Wenjing Liu (Nature Communications, 2023)
Abstract Over the past few decades, exciton-polaritons have attracted substantial research interest due to their half-light-half-matter bosonic nature. Coupling exciton-polaritons with magnetic orders grants access to rich many-body phenomena, but has been limited by the availability of material systems that exhibit simultaneous exciton resonances and magnetic ordering. Here we report magnetically-dressed microcavity exciton-polaritons in the van der Waals antiferromagnetic (AFM) semiconductor CrSBr coupled to a Tamm plasmon microcavity. Using angle-resolved spectroscopy, we reveal an exceptionally high exciton-photon coupling strength, up to 169 meV, demonstrating ultrastrong coupling that persists up to room temperature. By performing temperature-dependent spectroscopy, we show the magnetic nature of the exciton-polaritons in CrSBr microcavity as the magnetic order changes from AFM to paramagnetic. By applying an out-of-plane magnetic field, we achieve effective tuning of the polariton energy while maintaining the ultrastrong exciton-photon coupling strength. We attribute this to the spin canting process that modulates the interlayer exciton interaction.